Concrete Testing Device for In-Site Strength Evaluation and Aging Prediction of RCC Structures - Vinay Gowda D J,; Tarun B G,; Sudarshan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
In-situ compressive strength and rate of degradation over time are key factors in determining the longevity and dependability of reinforced cement concrete (RCC) constructions. The rebound hammer test and destructive core testing are two examples of traditional techniques that are time-consuming, expensive, and sometimes inappropriate for newly built or important buildings. This study describes the design and development of a small, inexpensive, and non-destructive concrete testing tool that may be used on-site to assess the strength and remaining service life of concrete components. In order to measure and visualise data in real time, the system interfaces a number of sensors, including piezoelectric vibration sensors, a temperature sensor, a capacitive moisture sensor, and an accelerometer-gyroscope module, with an microcontroller and an OLED display. In order to determine compressive strength, the device analyses vibration responses and ultrasonic pulse velocity (UPV) from the piezoelectric sensors. Temperature and moisture data are used as adjustment factors to increase accuracy. To evaluate material stiffness and ageing behaviour, the accelerometer-gyroscope module offers further vibration and damping data. Both the instantaneous strength and the predicted ageing factor of the tested RCC element are calculated by processing the recorded values using empirical and regression-based models. According to experimental validation, the suggested device offers improved mobility, shorter testing times, and easier operation while achieving near agreement with conventional non-destructive testing (NDT) techniques. The device's small size and multi-sensor fusion capabilities make it perfect for field engineers and construction workers to perform continuous inspections of concrete constructions in both new and existing buildings.
Keywords: Microcontroller; Temperature Sensor; Moisture Sensor; Concrete Strength Monitoring; Non-Destructive Testing (NDT); IoT-Based Structural Health Monitoring